Analisis Perbandingan Metode Multimedia Development Live Cycle Pada Augmented Reality - Naufal Afif Hawari; Erwin Dwika Putra (Jurnal Media Infotama, 2022)
Indonesia is one of the countries that has high biodiversity. This biodiversity is spread throughout the territory of Indonesia. However, endemic and rare animals in Indonesia are increasingly decreasing due to human greed. If this continues, the endangered species are likely to become extinct. therefore the need for an information media that is different from the usual, namely with Augmented Reality. Augmented Reality is a technology that can combine the real world with the virtual world and can combine the real world with virtual objects in it. In this research, augmented reality is used as a media of information and to learn about the biodiversity of the people, especially the animals that exist in Indonesia. This study aims to test the best method for making Augmented Reality. In this application, it displays 3D objects from deer animals. There are 4 menus in the application, one of which is detailed information about deer animals. objects can appear if the marker can be detected properly in the program. Key Words : Augmented Reality, Multimedia Development Live Cycle, Android